Financial Versus Monetary Mercantilism : Long-Run View of Large International Reserves Hoarding - Lee, Jaewoo; Aizenman, Joshua (Washington, D.C. : International Monetary Fund, 2006)
The sizable hoarding of international reserves by several East Asian countries has been frequently attributed to a modern version of monetary mercantilism-hoarding international reserves in order to improve competitiveness. From a long-run perspective, manufacturing exporters in East Asia adopted financial mercantilism-subsidizing the cost of capital- during decades of high growth. They switched to hoarding large international reserves when growth faltered, making it harder to disentangle the monetary mercantilism from a precautionary response to the heritage of past financial mercantilism. Monetary mercantilism also lowers the cost of hoarding through its short-term boost to external competitiveness, but may be associated with negative externalities leading to competitive hoarding.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet